Awareness of Age-Related Gains and Losses and Their Associations With Psychological Well-Being: A Longitudinal Examination. (19th August 2021) - Wilton-Harding, Bethany; Windsor, Tim D
Abstract: Objectives: How people experience their own aging is more strongly linked to well-being than chronological age. This study examined associations of awareness of age-related change (AARC) with between-person differences and longitudinal changes in psychological well-being (PWB). We expected that higher AARC gains would be associated with higher PWB and increases in PWB over time. Conversely, we expected higher AARC losses would be associated with lower PWB and a steeper decline in PWB over time. Furthermore, we tested the interaction of AARC gains and AARC losses to examine whether negative associations between AARC losses and PWB would be weaker among those reporting higher AARC gains. Methods: Data were collected in 3 waves from a 12-month longitudinal study of 408 community-dwelling older adults (aged 60 and older). Multilevel growth models were used to analyze associations between AARC and a composite measure of PWB which included key components of PWB identified in self-determination theory (satisfaction and frustration of basic psychological needs), as well as vitality, and life engagement. Results: At the between-person level, higher AARC gains and lower AARC losses was consistently associated with higher PWB. Furthermore, associations between AARC losses and lower PWB were weaker among those with higher AARC gains. There was no evidence to suggest the interplay of AARC gains and AARC losses had implications for change in PWB over time. Discussion: Appreciation of age-related gains may buffer the impact of AARC losses on PWB. However, longitudinal studies conducted over varying macro- and micro-time scales are needed to better understand the developmental significance of AARC for later life.